Study of the exogenous hormonal regulation of leaf senescence in two millets, Setaria italica, l. and Pennisetum typhoides, burm - Mahapatra, Mamata; Kumar, K. Bijay; Mohanty, B. K. (International Journal of Biological Research, 2016)
The present project is aimed at studying the exogenous regulation of leaf senescence in two millets i.e. Setaria italica, L. and Pennisetum typhoides Burm. The present study is confined to the study of excised leaf senescence by using growth regulators as the exogenous agents. Attached leaf study was avoided for the reason that preliminary experiments showed insensitiveness of the leaves of these two millets to growth regulators in the attached condition. In this study three growth regulators were selected, each from three major groups. Benzimidazole (BZI) represented cytokinins and indole acetic acid represented the auxins and GA3 represented Gibberelic Acid. In the present investigation, a significant negative correlation between RNA loss and RNase activity was found in both S.italica and P.typhoides. This suggests RNase like chlorophyllase responsible for bio-molecular breakdown. DNase activity was stable, it's activity increasing either in the first 72 h or up to the end of the incubation, but DNase activity decreased with time. Thus there was no correlation between the two. Acid phosphatase activity did not show any correlation with the established parameters of senescence, thus in both the plants the activity of the enzyme cannot be treated as an indicator of senescence. Among the two pyrophosphatases, alkaline enzyme showed a parallelism with the changes in chlorophyll and can be used as a reliable indicator of the process. On the other hand acid inorganic phosphatase activity increased during the incubation, but had no significant relation with other senescence related changes, suggesting more investigations to ascertain the role of acid inorganic pyrophosphatase.